Between grief and silence: Women's mental health after gestational loss (Research, Society and Development, 2026)
Pregnancy loss is an event with a significant emotional and psychological impact, capable of triggering feelings of sadness, guilt, frustration, and existential emptiness, which significantly compromise a woman's mental health. This article analyzed the impacts of pregnancy loss on women's mental health, considering the emotional and social implications and the role of support offered by healthcare professionals, especially nurses. This qualitative and exploratory study consists of a systematic literature review aimed at analyzing the impacts of pregnancy loss on women's mental health and identifying the role of multidisciplinary support, especially nursing, in coping with grief. Eight articles published between 2020 and 2025, selected from national and international databases, were included. The results indicated that the absence of adequate support, sensitive communication, and psychological assistance contributes to the worsening of suffering and increases the risk of pathological grief, anxiety, and depression. In contrast, the role of nursing, combined with multidisciplinary support, proved essential in providing active listening, guidance, continuous monitoring, and necessary referrals, favoring the reinterpretation of loss and the development of resilience strategies. It is concluded that valuing this experience and implementing humanized care protocols are fundamental for promoting women's mental health and strengthening the family and social support network.